Experimental investigation on the performance of a very high temperature heat pump with water refrigerant. (1st January 2020) - Wu, Di; Jiang, Jiatong; Hu, Bin; Wang, R.Z.
Abstract: Vapor compression very high temperature heat pumps (VHTHPs) with low-GWP refrigerants have attracted enormous attention for waste heat recovery. To yield high temperature output, a water vapor twin-screw compressor with water-injection is developed and a VHTHP prototype is established to conduct the experimental investigation. The experimental results show that when condensation temperature increases from 111 °C to 150 °C, the COP of this VHTHP decreases from 6.10 to 1.96 at the evaporation temperature of 85 °C. The highest COP is about 6.10 with the heating capacity of 285 kW at 85 °C evaporation and 117 °C condensation temperature, respectively. The highest condensation temperature of this water vapor VHTHP can reach 150 °C with the COP of 1.96. At the same temperature lift, the COP increases with the output temperature increasing. That means this VHTHP is more suitable for higher output temperature with the same temperature lift. So this VHTHP can be used to supply pressured hot water or high temperature steam when the user is favorable. Considering the characteristic of high-efficiency and environment-friendly, this VHTHP is highly desirable and competitive. Highlights: A water vapor VHTHP system was proposed to recover industry waste heat. A prototype of this water vapor VHTHP was set up to study its performance. The output temperature can reach 150 °C with the temperature lift of 65 °C. The water vapor VHTHP shows great performance at high temperature output.